1987
DOI: 10.1128/aac.31.12.1882
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin treatment of respiratory syncytial virus infections in infants and young children

Abstract: Respiratory syncytial virus (RSV)-infected cotton rats (Sigmadon hispidus) and owl monkeys (Aotus trivirgatus) showed significant reductions in RSV shedding from their respiratory tracts following parenteral therapy with human intravenous immunoglobulin (IVIG) containing high titers of RSV-neutralizing antibody. Because this therapy was well tolerated and appeared safe, a double-blind, placebo-controlled IVIG immunotherapy pilot study was performed on 35 hospitalized, RSV-infected infants and children. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(62 citation statements)
references
References 32 publications
1
58
1
2
Order By: Relevance
“…To identify transcripts that may be related to the difference in phenotype with the induction of infection, the transcripts that differed between C57BL/6J and AKR/J mouse lungs at any time point (6,12,24,48,96, or 192 h) were identified using a statistical threshold of an FDR of Ͻ0.05 (equivalent to an error probability of ϳ0.01), a Ն3.5-fold difference, and an average intensity of Ն80 fluorescence units. These criteria yielded a total of 1,389 elements consisting of 1,350 unique transcripts (i.e., 39 elements were duplicates or triplicates) and included 1,121 annotated genes, 190 nonannotated RIKEN cDNAs (DNA sequences deposited in the RIKEN Bioresource Center Data Bank), and 39 unnamed or pseudogenes.…”
Section: Resultsmentioning
confidence: 99%
“…To identify transcripts that may be related to the difference in phenotype with the induction of infection, the transcripts that differed between C57BL/6J and AKR/J mouse lungs at any time point (6,12,24,48,96, or 192 h) were identified using a statistical threshold of an FDR of Ͻ0.05 (equivalent to an error probability of ϳ0.01), a Ն3.5-fold difference, and an average intensity of Ն80 fluorescence units. These criteria yielded a total of 1,389 elements consisting of 1,350 unique transcripts (i.e., 39 elements were duplicates or triplicates) and included 1,121 annotated genes, 190 nonannotated RIKEN cDNAs (DNA sequences deposited in the RIKEN Bioresource Center Data Bank), and 39 unnamed or pseudogenes.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, passively administered monoclonal antibodies (MAbs) to the fusion (F) glycoprotein of the virus have been found protective and, among these, those capable of neutralizing and inhibiting the fusion function of the virus in vitro are most effective . In human infants, immune globulin with high virus neutralizing activity administered intravenously has been found to be of therapeutic value (Hemming et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Ribavirin was combined with IVIG because studies in vitro, in animal models, and in children had suggested that immunoglobulin may be of benefit for RSV infections prophylactically as well as therapeutically. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition, the University of Texas MD Anderson Cancer Center (MDACC) experience with combination aerosolized ribavirin and IVIG for the therapy of RSV pneumonia in adult BMT recipients and adults with leukemia had been favorable. 6,8 Bone Marrow Transplantation…”
mentioning
confidence: 99%